Pd-, Cu-, and Ni-Catalyzed Reactions: A Comprehensive Review of the Efficient Approaches towards the Synthesis of Antibacterial Molecules - Almeera Zia; Shehla Khalid; Nasir Rasool; Nayab Mohsin; Muhammad Imran; Sebastian Ionut Toma; Catalin Misarca; Oana Andreescu (MDPI AG, 2024)
A strong synthetic tool for many naturally occurring chemicals, polymers, and pharmaceutical substances is transition metal-catalyzed synthesis. A serious concern to human health is the emergence of bacterial resistance to a broad spectrum of antibacterial medications. The synthesis of chemical molecules that are potential antibacterial candidates is underway. The main contributions to medicine are found to be effective in transition metal catalysis and heterocyclic chemistry. This review underlines the use of heterocycles and certain effective transition metals (Pd, Cu, and Ni) as catalysts in chemical methods for the synthesis of antibacterial compounds. Pharmaceutical chemists might opt for clinical exploration of these techniques due to their potential.